Collagenous Fibroma (Desmoplastic Fibroblastoma): Different Localization. A Case Report+ (Annals of Medical Research, 2021)
None
Keywords: Collagenous fibroma, Desmoplastic fibroblastoma, Soft tissue tumors, Immunohistochemistry